Increasing genetic diversity of Salmonella enterica serovar Typhi isolates from Papua New Guinea over the period from 1992 to 1999 - Thong, Kwai Lin; Goh, Yee Ling; Yasin, Rohani M.; Lau, Ming Guek; Passey, Megan; Winston, Gibson; Yoannes, Mition; Pang, Tikki; Reeder, John C. (American Society for Microbiology, 2002)
Pulsed-field gel electrophoresis (PFGE) of XbaI-digested chromosomal DNA was performed on 133 strains of Salmonella enterica serovar Typhi obtained from Papua New Guinea, with the objective of assessing the temporal variation of these strains. Fifty-two strains that were isolated in 1992 and 1994 were of one phage type, D2, and only two predominant PFGE profiles, X1 and X2, were present. Another 81 strains isolated between 1997 and 1999 have shown divergence, with four new phage types, UVS I (n = 63), UVS (n = 5), VNS (n = 4), and D1 (n = 9), and more genetic variability as evidenced by the multiple and new PFGE XbaI profiles (21 profiles; Dice coefficient, F = 0.71 to 0.97). The two profiles X1 and X2 have remained the stable, dominant subtypes since 1992. Cluster analysis based on the unweighted pair group method using arithmetic averages algorithm identifies two main clusters (at 87% similarity), indicating that the divergence of the PFGE subtypes was probably derived from some genomic mutations of the X1 and X2 subtypes. The majority of isolates were from patients with mild and moderate typhoid fever and had various XbaI profiles. A single isolate from a patient with fatal typhoid fever had a unique X11 profile, while four of six isolates from patients with severe typhoid fever had the X1 pattern. In addition, 12 paired serovar Typhi isolates recovered from the blood and fecal swabs of individual patients exhibited similar PFGE patterns, while in another 11 individuals paired isolates exhibited different PFGE patterns. Three pairs of isolates recovered from three individuals had different phage types and PFGE patterns, indicating infection with multiple strains. The study reiterates the usefulness of PFGE in assessing the genetic diversity of S. enterica serovar Typhi for both long-term epidemiology and in vivo stability and instability within an individual patient.